Development of Genially Game-Based Interactive Learning Media on The Islamic Cultural History at MTs Al-Jauharotunnaqiyyah Cibeber - Maulana, Kiki; Zuhri, Saefudin; Febriani, Ina Salmah (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This research is motivated by the low engagement of student in the Islamic Cultural History learning process, which has impacted the low achievement of student learning outcomes. The aim of this study is to develop an interactive Genially-based learning media in the subject of Islamic Cultural History at MTs Al-Jauharotunnaqiyyah Cibeber. The research method used is Research and Development (R&D) with the Plomp development model. The result of this study are: 1) Describing the development procedures, which consist of five stages: a) prelimenary investigation, b) design, c) realization/construction, d) test, evaluation, revision, and, e) implementation. 2) Assessing the feasibility of the media through three expert validators, the average validation score from experts was 94%, categorized as ‘very feasible’. 3) Assessing the practicality of the media through questionnaires filled out by teacher and the students. The practicality score obtained an average of 94%, categorized as ‘very practical’. 4) Evaluating the effectiveness of the media through the implementation of pre-test and post-test. The result show a 67% increase in student learning outcomes, categorized as significant.